Recent Foraminifera From the Mahanadi River Estuary, East Coast of India - G, Swathi; B, Chandrika Sree; T, Sankara Rao; K, Mallikarjuna; K, Sai Kiran; G, Veeraswamy (International Journal of Membrane Science and Technology, 2023)
The Mahanadi River estuary (Figure 1) is one of the major estuaries in India and the largest one in the Odisha State. It is situated within latitudes 190 47? and 200 30? N and longitudes 850 33? and 860 49? E. It originates from Amarakantak region of Madhya Pradesh and flows through Madhya Pradesh and Odisha States over a length of 890 kms having a drainage basin of about 1,41,600 sq. kms with a large catchment area. It opens into the Bay of Bengal at Pardeep in Cuttack district. It has a wide opening into the sea at its northeastern end. The tidal stretch extends up to 32 kms from the mouth. The entire area is full of mangrove vegetation together with mud flats traversed by a network of tidal creeks except some portions such as Paradeep and Astaranga mouth regions which are sandy shorelines. The studies on Recent foraminifera in relation to the prevailing ecological parameters such as salinity, temperature, dissolved oxygen, and pH, and sediment characteristics and organic matter content of the sediments have been carried out in the present investigations. These studies can be used to delineate the palaeo-environments which serve as useful tools in the exploration for petroleum. 10 sediment and 10 water samples were collected from the estuary for the study of foraminifera and sediment characters, and water analysis respectively. The foraminifera of the estuary were identified. 12 abundant species which are Ammobaculities exiguus, Ammonia beccarii, Ammonia beccarii tepida, Elphidium advenum, Elphidium hispidulum, Milliamina fusca, Nonion depressulus, Pararotalia nipponica, Pararotalia cf. globosa, Quinqueloquelina lamarckina, Quinqueloculina seminulum and Rosalina globularis and are related to the prevailing ecological parameters and the substrate characteristics including the organic matter content.